Prehistoric history in Swedish primary school education: pupils' expression of empathy after visiting a cultural heritage site - Almqvist Nielsen, Lena (Education 3-13, 2025)
This study explores the concept of historical empathy in the context of field trips for young pupils to a prehistoric heritage site in Sweden. The example discussed is a field trip to Vitlycke, a heritage and rock carving site with an associated reconstructed Bronze Age farm, where pupils had the opportunity to experience prehistory with all their senses. The study is based on the idea that historical empathy is a process that involves both cognitive and affective dimensions and that both dimensions are important for progress. The pupils were interviewed after the trip and their responses are related to the concepts of perspective recognition and care. The study shows how the cognitive and affective dimensions were interwoven in the pupils' reasoning and how the field trip contributed to an emotional and personal connection necessary for the development of historical empathy. This engagement led to a broadening and deepening of the pupils' cognitive understanding of Bronze Age life and living conditions, while the cognitive understanding of the historical context contributed to a framework in which they could use their imagination. The results also show the importance of giving pupils time to follow up on their experiences after visiting a heritage site.